High-throughput sequencing of 16S rRNA gene analysis reveals novel taxonomic diversity among vaginal microbiota in healthy and affected sows with endometritis - Liang, Huixian (2023)
In sows afflicted with endometritis, vaginal microbiota can provide valuable information regarding bacterial community diversity. Our aim was to compare the vaginal microbiotas between endometritis and healthy sows and characterize the vaginal microbiota of endometritis sows using high-throughput sequencing of the 16S rRNA gene. Vaginal swabs were collected from healthy (Healthy_A, n = 10; Healthy_B, n = 10) and diseased (Endometritis_A, n = 10; Endometritis_B, n = 10) sows from two swine farms located in Guangdong and Yunnan province, in Southern China. The results of V3-V4 region of the 16S rRNA gene showed that Corynebacterium_1, Clostridium_sensu_stricto_1, Porphyromonas, Anaerococcus, Streptococcus, and Bacteroides comprised the core microbiota in all healthy sows. Two type of endometritis microbiota patterns were presented in two farms: the first comprised mostly of Burkholderia in farm A and the second comprised of Parvimonas in farm B. In farm A, the percentages of Burkholderia, Serratia, and Enterobacter were higher in the endometritis group, while only Parvimonas was significantly increased in the endometritis group in farm B (p < 0.05). Interestingly, the genus Burkholderia and Serratia were found only in the endometritis sows from farm A. Burkholderia was the most dominant genus found in endometritis sows and was confirmed by full-length 16S rRNA analysis using PacBio sequencing.